Evaluation of the Adsorption Efficiency of Glycine-, Iminodiacetic Acid -, and Amino Propyl-Functionalized Silica Nanoparticles for the Removal of Potentially Toxic Elements from Contaminated Water Solution. (4th January 2021) - Alswieleh, Abdullah M.; Albahar, Hajar Y.; Alfawaz, Amal M.; Alsilme, Abdulilah S.; Beagan, Abeer M.; Alsalme, Ali M.; Almeataq, Mohammed S.; Alshahrani, Ahmed; Alotaibi, Khalid M.
Abstract : In present work, mesoporous silica nanoparticles (MSNs) were prepared with a surface area of 1048 m 2 g -1 and a large pore size of ca. 6 nm, using Stöber process in the presence of expanding reagent (n -hexane). The surface of MSNs was modified with three different functional groups (amine, iminodiacetic acid, and glycine) and characterized by a variety of physicochemical techniques. The adsorption studies were carried out at different pH values in two extraction systems. In batch method, the maximum adsorption efficiency of heavy metals was measured to be 95% for all fabricated MSNs at pH 9. At pH 3, the adsorption efficiency of Pb and Cu was observed to be affected by the carboxylic moiety involved in the functional group. As the number of carboxylic moieties increase, the removal efficiency of Pb and Cu ions increased by two folds. The results demonstrated the selectivity of IDA-MSNs for the removal of Pb and Cu ions, even though the multielements are present in an aqueous solution. On the other hand, the incorporation of MSNs into the polymeric membrane showed high water permeability (9.96 ± 3 L / m 2 . h . bar ), and 98% rejection was achieved at pH 7 for Cu +2 and Pb +2 ions.